Susceptibility of adults of the cerambycid beetle Hedypathes betulinus to the entomopathogenic fungi Beauveria bassiana, Metarhizium anisopliae, and Purpureocillium lilacinum - Schapovaloff, M.E. (2014)
Fil: Schapovaloff, M.E.. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios en Parasitología y Vectores; Argentina